Informalidade, empreendedorismo e trabalho por conta própria: a naturalização do trabalho precário nas trajetórias de trabalhadores de comida de rua - Oliveira, Eveline Nogueira Pinheiro de (2023)
This is a thesis produced in the context of the Postgraduate Program in Psychology at UFC, that discusses the contemporary world of work in the face of new types of alternative jobs in the Brazilian scenario, in which informal work and entrepreneurship stand out as marks of the labor organization system. This work is the result of a larger research project that seeks to understand some of the most recent movements in capitalism: labor precarization, entrepreneurship, flexibilization, and the incorporation of informal work in the new ways of living. It is produced from the standpoint of labor studies and the Social Psychology of Work (PST). In a study of longitudinal inspiration, a rescue of interviews conducted with street food workers in the year 2017 was made, carried out in the course of the research for the author's master's degree. Considering the speed with which work is transforming and the pandemic crisis that took place in 2020, it was questioned how the working life of those same workers interviewed in 2017 was organized at the present moment. In this sense, self-reference interviews were conducted: the objective was to seek these subjects again and reminisce about the previous interview to understand their work history in this period. The analysis of the stories of working life, from the analytical standpoint of the occupational-paths theory, served to understand a broader movement in the life history of these workers: what could be called the entrepreneurial movement, which translates into precarization and volatility in the workers’ reality. What seems understandable is that conditions were created for the amplification of the reference to entrepreneurship as a policy to confront a fragile State in the conduction of the capital-labor relation, and as a mechanism to spread individualism and precarization disseminated in the labor sphere.